2019
DOI: 10.1371/journal.pone.0222449
|View full text |Cite
|
Sign up to set email alerts
|

Sputum microbiota and inflammation at stable state and during exacerbations in a cohort of chronic obstructive pulmonary disease (COPD) patients

Abstract: BackgroundExacerbations of chronic obstructive pulmonary disease (COPD) are debilitating events and spur disease progression. Infectious causes are frequent; however, it is unknown to what extent exacerbations are caused by larger shifts in the airways’ microbiota. The aim of the current study was to analyse the changes in microbial composition between stable state and during exacerbations, and the corresponding immune response.MethodsThe study sample included 36 COPD patients examined at stable state and exac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
3
17
1
Order By: Relevance
“…The main bacteria implicated are Haemophilus influenzae, Streptococcus pneumoniae, and Moraxella catarrhalis [62]. During the stable phase, longitudinal studies have identified a decrease in bacterial diversity and alteration in the systemic inflammatory response in pathways dependent on the bacterial response, such as TNF-α, IP-10, and MIG [63]. The use of antibiotics, such as azithromycin, usually used in COPD therapy to decrease the number of exacerbations, generates a decrease in bacterial diversity and an increase in microbial metabolites (glycolic acid, linoleic acid, and indole-3-acetate), resulting in altered expression of cytokines that regulate the immune response, such as IL-12, IL-13, CXCL-1, and TNF-α [40,45,64].…”
Section: Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%
“…The main bacteria implicated are Haemophilus influenzae, Streptococcus pneumoniae, and Moraxella catarrhalis [62]. During the stable phase, longitudinal studies have identified a decrease in bacterial diversity and alteration in the systemic inflammatory response in pathways dependent on the bacterial response, such as TNF-α, IP-10, and MIG [63]. The use of antibiotics, such as azithromycin, usually used in COPD therapy to decrease the number of exacerbations, generates a decrease in bacterial diversity and an increase in microbial metabolites (glycolic acid, linoleic acid, and indole-3-acetate), resulting in altered expression of cytokines that regulate the immune response, such as IL-12, IL-13, CXCL-1, and TNF-α [40,45,64].…”
Section: Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%
“…One-year treatment with ICS increases the total bacterial load in the sputum of COPD patients and changes the microbiome composition (13). Local inflammation in AECOPD is related to changes in the microbiota, characterized by reduced microbial diversity (14,15). Treatment with SCS alone decreased microbial alpha diversity in AECOPD (1).…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies comparing sputum microbiota between stable and exacerbated state in COPD indicate there are differences between disease states, but the findings are inconsistent [ 7 12 ]. And, two previous retrospective studies indicated that the sputum microbiota in the stable state was different in patients prone to exacerbations compared to patients who do not exacerbate [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%